Fifth-degree B-spline solution for nonlinear fourth-order problems with separated boundary conditions - Çağlar, Hikmet; Çağlar, Nazan; Özer, Mehmet (IOP PUBLISHING LTD, DIRAC HOUSE, TEMPLE BACK, BRISTOL BS1 6BE, ENGLAND, 2008)
In this paper, we discussed a fifth-degree B-spline solution for the numerical solution to nonlinear fourth-order boundary value problems (BVPs) with separated boundary conditions. Two numerical examples are given to illustrate the efficiency and performance of the method. The method gives accurate results for both the linear and nonlinear cases.
Keywords: finite-difference method; engineering applications; numerical-solution; equations; sonlu farklar yöntemi; mühendislik uygulamaları; sayısal çözüm; denklemler